SPECIFITY TECHNICAL RESEPTION OF UKRAINIAN EMBROIDERY - T.P. Stefanyuk (Academy of Cognitive and Natural Sciences, 2022)
In the article use different reception o f Ukrainian national embroidery in decorative products is considered (examined).